Neurocognitive function in patients with atrial fibrillation undergoing pulmonary vein isolation - Zwimpfer, Leon; Aeschbacher, Stefanie; Krisai, Philipp; Coslovsky, Michael; Springer, Anne; Paladini, Rebecca E.; Girod, Marc; Hufschmid, Janik; Knecht, Sven; Badertscher, Patrick; Beer, Jürg H.; Bonati, Leo H.; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Atrial fibrillation (AF) is associated with cognitive dysfunction. However, neurocognitive function in AF patients undergoing pulmonary vein isolation (PVI) has not been well studied. The aim of this analysis is to compare neurocognitive function in patients who did or did not undergo PVI. Materials and methods We used data from the Swiss Atrial Fibrillation Cohort study (Swiss-AF), a prospective, observational, multicenter study in Switzerland. Patients with documented AF were enrolled and data of 1,576 patients without history of PVI and with complete information on PVI status and neurocognitive function were used. Information on PVI was collected at baseline and during 1 year of follow-up. Neurocognitive testing was performed at baseline and after 1 year of follow-up, using the Montreal Cognitive Assessment (MoCA), trail making test (TMT) A and B, digit symbol substitution test (DSST) and semantic fluency test (SFT). To investigate the association of PVI with neurocognitive function, we use propensity score matching (1:3) and inverse probability of treatment weighting (IPTW). Results The mean age of this population was 74 ± 8 years, 27.1% were women. Overall, 88 (5.5%) patients underwent PVI during 1 year of follow-up. Using ITPW (n = 1576), PVI was weakly associated with the MoCA score after adjusting for time since PVI, baseline MoCA score and other covariates (β (95%CI) 1.19 (0.05; 2.32), p = 0.04). In the propensity matched comparison (n = 352), there was no significant association between PVI and the MoCA score (β (95%CI) 1.04 (−0.19; 2.28), p = 0.1). There were no significant associations between PVI and cognitive function when using the TMT A and B, DSST or SFT independent of the method used. Conclusion In this population of AF patients, there was no consistent evidence of an association between PVI and neurocognitive function. Clinical trial registration [https://clinicaltrials.gov/], identifier [NCT02105844].